1979
DOI: 10.1073/pnas.76.1.303
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of wild-type and variant mouse 3T3 cells with lectins from Bandeiraea simplicifolia seeds.

Abstract: An isolectin derived from Bandeiraea simplicifolia seeds and s ecific for terminal a->-galactopyranosyl groups was found tobe cytotoxic to Swiss 3T3 mouse cells. Alter mutagenesis and selection with BS I-B4, a variant clonal cell line resistant to both this isolectin and the a-D-and f-Dfalactose-binding lectin abrin was isolated. The parental cell fine showed homogeneous and noninteracting binding sites for BS I-B4, whereas the variant cells exhibited a curved plot with a reduced number of binding regions. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This again Analysis of protein transport by glycosylation mutants suggests unique translocator proteins must exist for different nucleotide sugars (Perez & Hirschberg, 1986;Hirschberg & Snider, 1987). Several other mutants exhibiting a similar phenotype have been isolated: PHARI .8 from the mouse lymphoma cell line BW5127, (Trowbridge et al, 1978;Duncan & Kornfeld, 1988); BSI.B4 from the mouse fibroblast cell line 3T3 (Stanley et al, 1979); MDW4 from the tumour cell line MDAY-D2 (Dennis, 1986), and Al from the rat pheochromocytoma cell line PC 12 (Green & Kelly, 1990).…”
Section: Parental Linementioning
confidence: 86%
“…This again Analysis of protein transport by glycosylation mutants suggests unique translocator proteins must exist for different nucleotide sugars (Perez & Hirschberg, 1986;Hirschberg & Snider, 1987). Several other mutants exhibiting a similar phenotype have been isolated: PHARI .8 from the mouse lymphoma cell line BW5127, (Trowbridge et al, 1978;Duncan & Kornfeld, 1988); BSI.B4 from the mouse fibroblast cell line 3T3 (Stanley et al, 1979); MDW4 from the tumour cell line MDAY-D2 (Dennis, 1986), and Al from the rat pheochromocytoma cell line PC 12 (Green & Kelly, 1990).…”
Section: Parental Linementioning
confidence: 86%
“…Recently, we have demonstrated that both CHO and BHK cells are resistant to killing in 40% human seram (data not shown). Altematively, the selection of glycosylation mutants from preexisting VPC lines based on IB4 lectin or human serum sensitivity could be utilized (Stanley et al, 1979;Tsuruoka et al, 1993). These strategies of generating human serum-resistant VPC and retroviral particles are currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…The human erythrocytes were provided by W. John Judd, Department of Pathology, University of Michigan, and were obtained from normal blood donors. The parent Swiss 3T3 cells and a variant line of 3T3 cells deficient in terminal a-D-galactopyranosyl groups (3T3 Bdr) were obtained from Dr Barry Peters, Department of Pharmacology, University of Michigan, and have been described in a previous report [6]. Murine L-929 cells, and a variant of the L-929 cells deficient in surface a-o-galactopyranosyl end groups (L-929 Abn') were obtained from Dr E. H. Y. Chu.…”
Section: Cellsmentioning
confidence: 99%